Green jobs: supranational context, conceptual approaches and challenges for labour market policies - Monjas Barrena, Miriam (CUADERNOS DE DERECHO TRANSNACIONAL, 2025)
In a global scenario of “permacrisis” (economic, climatic, health-related, energy-related, etc.), the ecological transition toward a model of sustainable development has become a central issue for international and supranational policies and, consequently, for national policies and economies as well. This ecological transition has (and is already having) significant and unequal social impacts that must be managed as fairly as possible, particularly in terms of employment. Thus, the concept of a just transition emerges as a key framework to place social justice at the heart of ecological transitions. Its most relevant manifestation is green employment, which serves as a tool to overcome the challenges that the shift toward a green economy poses for national labor market policies.
Keywords: Green jobs; green transition; just transition; labor market policies